2021
DOI: 10.1371/journal.pone.0258274
|View full text |Cite
|
Sign up to set email alerts
|

The efficiency of provincial government health care expenditure after China’s new health care reform

Abstract: Objective We aim to estimate the total factor productivity and analyze factors related to the Chinese government’s health care expenditure in each of its provinces after its implementation of new health care reform in the period after 2009. Materials and methods We use the Malmquist DEA model to measure efficiency and apply the Tobit regression to explore factors that influence the efficiency of government health care expenditure. Data are taken from the China statistics yearbook (2004–2020). Results We fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Disparities in healthcare resources across the provinces increased following the economic reform, and the socioeconomic status is associated with healthcare resources ( Bakkeli, 2021 ). The eastern regions with better economic status and more healthcare investment have high-quality healthcare resources ( Guo et al, 2021 ). Residents from the affluent eastern regions are more likely to use preventive care than those from the central and northeastern regions ( Huang et al, 2016 ).…”
Section: Suggestions For the Improvement Of The Prevention And Contro...mentioning
confidence: 99%
“…Disparities in healthcare resources across the provinces increased following the economic reform, and the socioeconomic status is associated with healthcare resources ( Bakkeli, 2021 ). The eastern regions with better economic status and more healthcare investment have high-quality healthcare resources ( Guo et al, 2021 ). Residents from the affluent eastern regions are more likely to use preventive care than those from the central and northeastern regions ( Huang et al, 2016 ).…”
Section: Suggestions For the Improvement Of The Prevention And Contro...mentioning
confidence: 99%
“…Socio-economic indicators often used as outputs in measuring government efficiency are indicators in education (Dufrechou 2016;Gavurova et al 2017;Rambe 2020) and health (Guo et al 2021;Olanubi and Osode 2017). Education and health indicators are used as outputs because these two are the essential government services for the community.…”
Section: Output Used In Efficiency Measurementmentioning
confidence: 99%
“…International scholars have evaluated government funding and government intervention in the development of internet medical care and government-led medical insurance initiatives. They suggest that the Chinese government adhere to its new healthcare reform policy and pay attention to demographic and economic factors when implementing it [ 25 ]. Others have found that China’s policy interventions strongly promote the development of internet hospitals in China.…”
Section: Literature Viewmentioning
confidence: 99%